Sufficient Statistics for Frictional Wage Dispersion and Growth - Rune Vejlin; Gregory F. Veramendi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper develops a sufficient statistics approach for estimating the role of search frictions in wage dispersion and lifecycle wage growth. We show how the wage dynamics of displaced workers are directly informative of both for a large class of search models. Specifically, the correlation between pre- and post-displacement wages is informative of frictional wage dispersion. Furthermore, the fraction of displaced workers who suffer a wage loss is informative of frictional wage growth and job-to-job mobility, independent of the job-offer distribution and other labor-market parameters. Applying our methodology to US data, we find that search frictions account for less than 20 percent of wage dispersion. In addition, we estimate that between 40 to 80 percent of workers experience no frictional wage growth during an employment spell. Our approach allows us to estimate how frictions change over time. We find that frictional wage dispersion has declined substantially since 1980 and that frictional wage growth, while low, is more important towards the end of expansionary periods. We finish by estimating two versions of a random search model to show how at least two different mechanisms—involuntary job transitions or compensating differentials—can reconcile our results with the job-to-job mobility seen in the data. Regardless of the mechanism, the estimated models show that frictional wage growth accounts for about 15 percent of lifecycle wage growth.
Keywords: E24; J31; J64; 330; search models; wage dispersion; wage growth; sufficient statistics; displacement